Private Product Computation Using Quantum Entanglement - Rene Bodker Christensen; Petar Popovski (IEEE Transactions on Quantum Engineering, 2023)
In this article, we show that a pair of entangled qubits can be used to compute a product privately. More precisely, two participants with a private input from a finite field can perform local operations on a shared, Bell-like quantum state, and when these qubits are later sent to a third participant, the third participant can determine the product of the inputs, but without learning more about the individual inputs. We give a concrete way to realize this product computation for arbitrary finite fields of prime order.